A 6-minute sub-maximal run test to predict VO2 max - Matabuena, M.; Vidal, J. C.; Hayes, P. R.; Trillo, F. H. (Journal of Sports Sciences, 2018)
Maximal oxygen uptake ( max) is a key indicator to assess health as well as sports performance. Currently, maximal exercise testing is the most accurate measure of maximal aerobic power, since submaximal approaches are still imprecise. In this paper, we propose a new method to predict max from a submaximal, low intensity, test in sports men and women. 182 males and 108 females from the High Performance Center of Pontevedra (Spain), aged 10-46 years old, with a max between 30.1 and 81.2 mL/min·kg, completed a maximal incremental test to volitional exhaustion. The test began at a speed of 6 km/h and increased by 0.25 km/h every 15 seconds. Using the data gathered during the first 6 minutes of the test, two different regression models were adjusted using functional data analysis and a traditional linear regression model with scalar covariates. The functional regression model obtained the best results, adjusted r2 = 0.845 and RMSE = 2.8 mL/min·kg, but the linear regression model also obtained a good fit, adjusted r2 = 0.798 and RMSE = 3.5 mL/min·kg. Both methods are more accurate than classical submaximal tests, although oxygen consumption needs to be measured during the test.